Komunikasi Antarbudaya Melalui Tradisi Perkawinan Suku Bajo dan Suku Samawa di Sumbawa Besar - Irga Fahdiran; Aurelius Rofinus Lolong Teluma; Muhammad Jamiluddin Nur (Program Studi Ilmu Komunikasi Universitas Mataram, 2021)
The people of West Nusa Tenggara, especially the Pulau Bungin Village, Alas District, cannot be separated from social interactions with other tribes around Alas District. Interactions often occur and lead to inter-ethnic marriages, such as the relationship that occurs between the Bajo tribe and the Samawa people who are married in Alas District, Sumbawa Regency. The research entitled Intercultural Communication Patterns Through the Marriage Tradition of the Bajo and Samawa Tribe in Pulau Bungin Village, Alas District, Sumbawa Regency. Aiming to see how the pattern of intercultural communication through the tradition of marriage is carried out by the Bajo tribe with the Samawa tribe in Pulau Bungin Village, Alas District, Sumbawa Regency. The theory used in this research is the symbolic interaction theory by George Herbert Mead (1863-1931). The research method used in this research is qualitative with a case study approach. The technique of collecting data is done through interviews, observation, and documentation. This study's data analysis techniques were carried out by data reduction, data presentation, and data validation by using source triangulation techniques and drawing conclusions.